Tribolium castaneum (Coleoptera: Tenebrionidae) associated with rice mills: fumigation efficacy and population rebound - Buckman, Karrie A.; Campbell, James F.; Subramanyam, Bhadriraju (My University, 2013)
The red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), is the most important stored-product insect pest infesting rice (Oryza sativa L.) mills in the United States. Due to the phasing out of methyl bromide in accordance with the 1987 Montreal Protocol, the efficacy of alternative fumigants in controlling flour beetles in mill structures must be evaluated. Long-term trapping data sets (2-6 yr) of T. castaneum in and around seven rice mills were analyzed to assess the efficacy of sulfuryl fluoride fumigation (n = 25). Fumigation efficacy was evaluated as the percentage reduction in mean trap captures of adults and proportion of traps capturing at least one adult beetle. Beetle trap captures fluctuated seasonally, with increased captures during the warmer months, June-September, that dropped off during the cooler months, October-March. Fumigations resulted in a 66 ± 6% (mean ± SE) reduction in mean trap captures within mills and a 52 ± 6% reduction in the proportion of traps capturing at least one adult beetle. Lengths of time for captures to reach prefumigation levels, or rebound rates, were variable, and adult capture levels inside were most influenced by seasonal temperature changes. Temperatures inside mills followed those outside the mill closely, and a significant positive relationship between outside temperatures and trap captures was observed. Inside and outside trap captures exhibited a significant, positive relationship, but fumigations consistently led to reductions in beetle captures outside of mills, highlighting the interconnectedness of populations located inside and outside mill structures.
Keywords: Red flour beetle; Fumigation; Sulfuryl fluoride; Pheromone trap; Monitoring